Off-pump versus on-pump redo coronary artery bypass grafting: a systematic review and meta-analysis. (October 2021) - Zhang, Pengbin; Wang, Liping; Zhai, Kerong; Huang, Jian; Wang, Weifan; Ma, Qi; Liu, Debin; Gao, Bingren; Li, Yongnan
Background: Redo coronary artery bypass grafting (redo CABG) is associated with increased mortality and morbidity. The aim of this study was to systematically evaluate the evidence comparing the outcomes of off-pump with on-pump redo CABG. Methods: Studies were systematically searched and identified using PubMed, EMBASE, the Cochrane Library, and the International Clinical Trials Registry Platform (ICTRP) by two researchers independently. The primary outcome was 30-day mortality, and the secondary outcomes were in-hospital mortality, post-operative complications, completeness of revascularization, blood transfusion rate, duration of mechanical ventilation, intensive care unit and hospital stays. Results: The 21 studies including 4, 889 patients were enrolled in our meta-analysis. Compared with on-pump, the off-pump technique was associated with significantly reduced 30-day mortality (odds ratio [OR] = 0.43, 95% confidence interval [CI] = 0.26-0.72, p = 0.001). Moreover, a notably decreased in-hospital mortality (OR = 0.55, 95% CI = 0.39-0.76, p = 0.0004) and incidence of post-operative new-onset atrial fibrillation, myocardial infarction, acute kidney injury, low cardiac output state, blood transfusion rate (OR = 0.46, 95% CI = 0.35-0.60, p < 0.00001; OR = 0.54, 95% CI = 0.38-0.78, p = 0.0007; OR = 0.51, 95% CI = 0.37-0.70, p < 0.0001; OR = 0.31, 95% CI = 0.20-0.47, p < 0.00001; OR = 0.29, 95% CI = 0.14-0.61, p = 0.001) and significantly shortened duration of mechanical ventilation, intensive care unit and hospital stays (mean difference [MD] = −8.21 h, 95% CI = −11.74 to −4.68, p < 0.00001; MD = −0.77 d, 95% CI = −0.81 to −0.73, p < 0.00001; MD = −2.24 d, 95% CI = −3.17 to −1.32, p < 0.00001) could be observed when comparing the outcomes of off-pump with on-pump redo CABG. There was nonsignificant difference between off-pump and on-pump redo CABG in completeness of revascularization. Conclusion: In patients undergoing redo CABG surgery, the off-pump technique was associated with decreased mortality, less post-operative complications when compared to on-pump.